Disrupting Spatiality and Temporality: Authority and Statecraft in Hikayat Mareskalek - Alatas, Ismail F. (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2009)
While this essay shares Stoler's analytical approach of literature, it does not focus on the politics of a?ect. Rather, this essay examines an early nineteenth century literary production, the Hikayat Mareskalek, in an attempt to question various assumptions in contemporary works on the Malay-Indonesian archipelago. The first is the perceived geography of culture that is divided over what is considered 'Malay' and what 'Javanese.' The second is a temporal construct where a break with the past in the form of modernity occurred as a result of the shock of the colonial encounter. This attempt is framed in the study of authority and statecraft envisioned in the Hikayat. The first part of the essay tries to locate the spatial context of the Hikayat while the second reconstructs ideas of authority and statecraft enshrined in the text.DOI: 10.15408/sdi.v16i3.474